Experience of shocks, household wealth and expectation formation: Evidence from smallholder farmers in Kenya - Hanna Freudenreich; Sindu W. Kebede (Agricultural Economics, 2022)
When faced with uncertain events, decision-makers form expectations about the events' likelihood of occurrence. However, the drivers and moderators of such expectations are still poorly understood, especially for farm decision-makers in developing countries whose incomes are very risky by nature. This article analyses the dynamic shock expectation formation process of farmers in Kenya with regard to a range of shock events using a unique panel dataset. The results suggest that farmers are more likely to update their expectation regarding a specific adverse shock when they have recently been affected by that shock or by more shocks in general. In case of price shocks, farmers are also more likely to update expectations when a larger proportion of fellow village members was affected. However, household wealth moderates the relationship between shock expectation and experience, such that wealthier households are less likely to update their expectations following a shock. A better understanding of the drivers of expectation formation can help in the design of better risk management instruments that increase farmers' resilience.
Keywords: 330; farmers; risk; shocks; subjective expectations